2022
DOI: 10.9734/aprj/2022/v9i430213
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity of Medicinal Plants of the Himalayan Kingdom of Bhutan

Abstract: Most nations depend heavily on plants as economic resources. They can be categorized according to their contribution to economic development thanks to their taxonomic classes. Plant components are used in pharmaceutical research and the creation of novel medications in the healthcare industry. Plant components or herbal concoctions are utilized as herbal medicines in Bhutan and other parts of the world to treat various illnesses. The study aimed to list all the plants possessing medicinal properties from the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Some residents have reported that collecting firewood from the forest is now forbidden (by the Forest Department). They chop off the tops, lops, and branches of trees cut for timber [39]. Fuelwood can also be harvested from dead trees.…”
Section: Fuelwoodmentioning
confidence: 99%
“…Some residents have reported that collecting firewood from the forest is now forbidden (by the Forest Department). They chop off the tops, lops, and branches of trees cut for timber [39]. Fuelwood can also be harvested from dead trees.…”
Section: Fuelwoodmentioning
confidence: 99%